2006
DOI: 10.1016/j.febslet.2006.01.077
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically enhanced cellular delivery of cell penetrating peptide‐PNA conjugates

Abstract: Recent studies have shown that endosomal release is a major rate-limiting step for cellular delivery via a variety of cationic cell penetrating peptides. Thus, methods and/or protocols for effective release of endosomally entrapped drugs are highly warranted. Photochemical internalization (PCI) has previously been proposed for this purpose. Here, we demonstrate an enhancement of up to two orders of magnitude of the antisense effects (cytosolic/nuclear) of peptide nucleic acid-peptide conjugates (Tat, Arg 7 , K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 16 publications
7
57
0
1
Order By: Relevance
“…However, PNA-CPP conjugates were released from the endosomal trap by addition of chloroquine (76). Splice correction by PNA-CPP and PMO-CPP conjugates using luciferase reporter gene has been achieved (77)(78)(79)(80)(81). In vitro CPP-mediated delivery of splice correcting ON analogs has been demonstrated for nuclear targeting (82).…”
Section: Delivery Of Nucleic Acids By Cpp-mediated Cargo Deliverymentioning
confidence: 99%
“…However, PNA-CPP conjugates were released from the endosomal trap by addition of chloroquine (76). Splice correction by PNA-CPP and PMO-CPP conjugates using luciferase reporter gene has been achieved (77)(78)(79)(80)(81). In vitro CPP-mediated delivery of splice correcting ON analogs has been demonstrated for nuclear targeting (82).…”
Section: Delivery Of Nucleic Acids By Cpp-mediated Cargo Deliverymentioning
confidence: 99%
“…First, the entry mechanism implies the use of pathways that are sensitive to lysosomotrophic agents, such as chloroquine and sucrose [57,58]. Moreover, the efficacy of the cell uptake is improved by coincubation of Tat with another peptide derived from the hemagglutinin protein which has membrane fusogenic properties [59], or by the use of photochemical internalization mediated by a membrane soluble photosensitizer [60].…”
Section: Cpps and Cell Entrymentioning
confidence: 99%
“…There is subsequent release of the entrapped drugs into the cytosol (Berg et al, 1999;Selbo et al, 2000a). PCI of numerous macromolecules has been demonstrated in vitro, including the 30-kDa ribosome-inactivating proteins gelonin and saporin (Berg et al, 1999), gelonin-and saporin-based targeting toxins (Selbo et al, 2000b;Weyergang et al, 2006), different peptide nucleic acids (Folini et al, 2003;Shiraishi and Nielsen, 2006), and DNA for gene therapeutic purposes both with viral and nonviral vectors (Hogset et al, 2004). Recently it was shown that using photosensitizers localizing to endocytic vesicles enhanced the delivery of adenoviruses to the nucleus after PCI treatment .…”
mentioning
confidence: 99%